Buying centers and emerging developments: The SME perspective - Cardinali, Silvio; Sharma, Piyush; Cedrola, Elena; Giovannetti, Marta; Pillai, Kishore Gopalakrishna (Emerald, 2023)
Purpose: This paper aims to explore the challenges and opportunities faced by buying centers in small and medium enterprises (SME) manufacturing companies in view of recent technological changes and the virtualization of communication.